Ambiguous symbols - Thomas, Julian (Documenta Praehistorica, 2005)
In this paper I discuss the scarcitz of representational art, and particularly of representations of the human body, in Neolithic Britain, in contrast with the Neolithic of south-east Europe. My suggestion is that this contrast can be linked with differing notions of personal identity and bodily integrity. In later Neolithic Britain, a complex mode of non-representational decoration developed, which elaborated the practice of making reference to absent persons and things bz using deliberately ambiguous motifs, which connected past and present as well as remote locations.
Keywords: Velika Britanija; arheološke najdbe; neolitik; navade; običaji; simboli; symbol